A Finite Element Analysis of Peri-implant Stresses Surrounding Zirconium and Titanium Dental Implants - MS Sabiha Kouser; M Prathibha; Omar Basheer Altaher Mohammed; Nureldeen AN Elhammali; Ahmad Saib Jameel; Meghna Chauhan; Kaushik Shetty (Journal of Pharmacy and Bioallied Sciences)
Introduction: Stresses tend to vary depending on the kind of implant material (titanium or zirconium) because of differences in their mechanical and physical characteristics. Objectives: The current research was done to assess the peri-implant stresses around zirconium and titanium dental implants using finite element analysis. Materials and Method: Three distinct implant configurations were used to create three-dimensional finite element models (M1, M2, and M3) using ANSYS (11.0 Version) software, a P4 CPU running at 3 GHz, and hardware with three gigabytes of RAM. These configurations are typical for zirconium and titanium implants. Under 250 N of axial force and 50 N of nonaxial load, the stress surrounding the implants was examined. Result: When compared to titanium implants, zirconium implants displayed higher strains in cancellous bone and lower stresses in cortical bone. Overall, titanium implants caused larger stresses in the bone than zirconium implants. Conclusion: Compared to titanium implants, zirconium implants resulted in reduced peri-implant stresses.